Penerapan Metode Fahim Qur’an Untuk Meningkatkan Hasil Belajar Siswa dalam Pembelajaran Tahfizh Alqur’an di SDIT Adzkia Padang - Novita, Yanti; Fitria, Aida; Ramadona, Eri (Jurnal Ilmiah Al-Furqan: Al-qur'an Bahasa dan Seni, 2023)
This study describes several findings about one application of the tahfizh method, namely the "Fahim Qur'an" method to improve student learning outcomes in learning tahfizh al-Qur'an. The learning outcomes can be seen from the evaluation carried out in several stages, namely new student ability tests, daily tests, EBTA memorizing letters, evaluation of holidays by reviewing student memorization, evaluation of semester exams for khatam al-Qur'an and memorization compre. Student learning outcomes using this method show good results in terms of quantity and quality.